2021
DOI: 10.1097/cad.0000000000001136
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide III induces apoptosis by regulating the Bax/Bcl-2 signaling pathway in human colorectal cancer HCT-116 Cells in vitro and in vivo

Abstract: Atractylodes is the dry root of atractylodes macrocephala koidz and has been commonly used as a traditional Chinese medicine (TCM). Atractylenolide III, a main component of atractylodes, has displayed significant effects on anti-inflammation and anticancer. However, the effects of atractylenolide III on growth inhibition and apoptosis induction in colon cancer remain unclear. The results showed that atractylenolide III significantly inhibited the cell growth and induce cellular apoptosis in HCT-116 cells in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“… 59 , 60 Therefore, we chose iNOS, Arg-1 and CD206 as indicators to detect macrophage polarization. Meanwhile, since BAX and Bcl2 are key factors in the process of apoptosis, 61 the correlation and ratio of the two determine the survival or death of cells after apoptotic stimulation. 62 Most of the studies have used the examination of BAX and BCL2 expression levels to verify apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 59 , 60 Therefore, we chose iNOS, Arg-1 and CD206 as indicators to detect macrophage polarization. Meanwhile, since BAX and Bcl2 are key factors in the process of apoptosis, 61 the correlation and ratio of the two determine the survival or death of cells after apoptotic stimulation. 62 Most of the studies have used the examination of BAX and BCL2 expression levels to verify apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…62 Most of the studies have used the examination of BAX and BCL2 expression levels to verify apoptosis. [61][62][63][64] Therefore, we likewise chose BAX and Bcl-2 as indicators to detect apoptosis. We found that human monocyte-derived macrophages co-cultured with KCs-oe-MALAT1-Exo possessed greater cytophagocytosis, weaker apoptosis and a greater tendency to polarize towards the M2 phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Grayscale analysis of the western blot images was conducted with Photoshop (Microsoft Corporation). 30…”
Section: Methodsmentioning
confidence: 99%
“…Hinesol, a compound extracted from Atractylodes Rhizoma application in the study of non-small cell lung cancer, induces proliferation, inhibition, and apoptosis in non-small cell lung cancer cell lines by up-regulating Bax and inhibiting the expression of Bcl-2 ( 40 ). Atractylenolide III is a kind of anti-inflammatory and anti-tumor active substance, that induces apoptosis of human colon cancer HCT-116 cells by promoting apoptosis-related genes, regulating the Bax/Bcl-2 apoptosis signaling pathway, and the expression of caspase-3 and p53 ( 41 ).…”
Section: Apoptosis and Immunogenic Cell Deathmentioning
confidence: 99%